2023
DOI: 10.3390/biomedicines11030890
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Organoids: An Emerging Platform for Precision Medicine?

Abstract: Despite recent therapeutic advances, pancreatic ductal adenocarcinoma (PDAC) remains one of the most aggressive malignancies, with remarkable resistance to treatment, poor prognosis, and poor clinical outcome. More efficient therapeutic approaches are urgently needed to improve patients’ survival. Recently, the development of organoid culture systems has gained substantial attention as an emerging preclinical research model. PDAC organoids have been developed to study pancreatic cancer biology, progression, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Conducting research focused on understanding the genetic and biological factors that contribute to PCa disparities is essential, which is often referred to as precision medicine. By unraveling the molecular underpinnings of disparities, researchers can develop targeted interventions and therapies to address specific genetic and biological vulnerabilities [112][113][114]. Ensuring diversity and representation in genetic research studies is critical to addressing disparities effectively.…”
Section: Genetic and Biological Factorsmentioning
confidence: 99%
“…Conducting research focused on understanding the genetic and biological factors that contribute to PCa disparities is essential, which is often referred to as precision medicine. By unraveling the molecular underpinnings of disparities, researchers can develop targeted interventions and therapies to address specific genetic and biological vulnerabilities [112][113][114]. Ensuring diversity and representation in genetic research studies is critical to addressing disparities effectively.…”
Section: Genetic and Biological Factorsmentioning
confidence: 99%
“…Recent advancements in scaffold fabrication techniques, encompassing electrospinning, lyophilisation, and 3D printing, facilitate the generation of structures with precisely regulated porosity, pore dimensions, fibre size/diameter, and interconnected architecture, which are imperative for cellular infiltration, nutrient and waste exchange, as well as vascularisation [85]. Conversely, 3D constructs synthesised via bioprinting methodologies, including laser-assisted, microextrusion-based, and inkjet bioprinting [27], offer the capacity for customisation in accordance with specific requirements. Moreover, incorporating growth factors or bioactive molecules into scaffolds can further augment their osteoinductive properties, promoting bone regeneration [86].…”
Section: Scaffolds For Bone Regenerationmentioning
confidence: 99%
“…Organoids are novel preclinical models that recapitulate complete or partial characteristics of their native organs and surpass 2D cell models' ability to mimic complex spatiotemporal development, regeneration, and disease processes (Figure 1). A growing body of evidence suggests that organoids are becoming a significant platform for the future of medicine and precision medicine, especially in the case of several cancers [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, amongst the models used, there is a fine difference between 3D spheroids and 3D organoids. The former is derived from monolayers of epithelial cells, which are cultured in low-attachment conditions that promote the formation of cell aggregates; the latter originates from tissues, or from adult or embryonic stem cells, using specific cell culture conditions [1]. In addition, spheroids may consist entirely of cancer cells (homotypic spheroids), or they can be co-cultured with other cellular types (heterotypic spheroids), allowing the study of more complicated cellular interactions within tumors than is possible with 2D cultures [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also reported that 2D and 3D cell cultures exhibit different degrees of sensitivity to cancer drugs, so 3D cultures are more appealing for pharmaceutical studies. For example, spheroids have been used to screen putative new anticancer compounds and to assess the response of individuals to chemotherapy; this can be seen as a step closer to precision chemotherapy [1]. A detailed comparison of 2D and 3D cultures, in which their properties and benefits are described, can be read in [2,6,7].…”
Section: Introductionmentioning
confidence: 99%